A decoupling network for resonant and non-resonant sub-1 GHz MIMO mobile terminal antennas with improved compactness and efficiency - Wai, Loon Cheor; Azremi, Abdullah Al-Hadi; Ping, Jack Soh; Mohd Faizal, Jamlos; Mohamed Elshirkasi, Ahmed; Chen, Xiaoming; Akkaraekthalin, Prayoot (IEEE, 2021)
In this work, the design procedure of a new decoupling network for different antennas is presented for mobile terminals operating in the Sub-1 GHz band (from 0.698 to 0.96 GHz). To evaluate its applicability for different resonant and non-resonant antenna types, two antenna elements have been chosen to be decoupled using the proposed decoupling network: a printed inverted-F antenna and a capacitive coupling element antenna. Simulation and measurement results showed that the decoupling network offer promising improvements in terms of impedance matching, port isolation, envelope correlation coefficient (ECC), and total efficiency. In addition, the antennas are also investigated with the ergodic capacity, multiplexing efficiency, gain, and diversity gain (both calculated using maximal ratio combining technique). Due to the contribution of the decoupling network, the ECC of both types of multiple antennas are less than 0.3, with a 30 % improvement in total efficiency and an inter-element spacing miniaturization of 34 %.